2006
DOI: 10.1016/j.apcatb.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation catalysts prepared from biosorbents supported on zeolites

Abstract: The catalytic oxidation of 1,2-dichlorobenzene was investigated over NaYand NaX zeolites, loaded with chromium through the action of a robust biosorption system consisting of a bacterial biofilm supported on the zeolites. The results of biosorption showed that the maximum metal removal efficiency was 20%, in both systems based on NaYor NaX, starting from solutions with chromium(VI) concentrations ranging from 50 to 250 mg Cr /L. The bacterial biofilm, Arthrobacter viscosus, supported on the zeolite reduces Cr(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…The reaction with diphenylcarbazide is nearly specific to Cr. [24]. These authors reported that a biofilm of A. viscosus supported on Y and X zeolites was able to remove chromium from dilute solutions (50-250 mg Cr(VI) per litre) with a maximum removal efficiency of 20 %.…”
Section: Experimental Procedures and Cr Removalmentioning
confidence: 94%
See 2 more Smart Citations
“…The reaction with diphenylcarbazide is nearly specific to Cr. [24]. These authors reported that a biofilm of A. viscosus supported on Y and X zeolites was able to remove chromium from dilute solutions (50-250 mg Cr(VI) per litre) with a maximum removal efficiency of 20 %.…”
Section: Experimental Procedures and Cr Removalmentioning
confidence: 94%
“…Figueiredo et al [24] reported an innovative process that combines the use of a zeolite and an A. viscosus biofilm to remove Cr(VI) in solution. They found that the A. viscosus bacteria supported on the zeolite reduce Cr(VI) to Cr(III), and the Cr(III) is retained in the zeolite by ion exchange.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition some microbe uses metal-cyano complexes as nitrogen source and for the dissociation of these complexes they form biofilm on the surface to adsorb metal ions or form siderophores. Siderophores are the iron sequestering compounds produced by microbes for iron chelating [37][38][39].…”
Section: Enzymatic Pathways For Cyanide Degradationmentioning
confidence: 99%
“…Clinoptilolite was characterized with the diffractions appeared at 9. Y-zeolite was a faujasite type mineral defined by the reflections at 6.3, 10.3 and 12.1 (2Â • ) [5,21,22,48,49]. Bare minerals and the composites had similar XRD patterns; there were not any distortions and shifts in any of the peaks, which predicated that the minerals were not deformed with inclusion of the hydrogel.…”
Section: Structural Evaluationmentioning
confidence: 98%